Development of the Science and Studies of Economics in Lithuania in the 20th Century - Martišius, Stanislovas (Ekonomika, 2000)
The article analyses the economic thought of the interwar Lithuania, studies of economics, in 1940-1990 and the reorganization of the science and studies of economics after the re-establishment of Lithuania’s independence.It has been established that:1. the doctrines of “directed Economy” were popular in the inter=war Lithuania;2. during the Soviet period, the attention of economists was focused on applied economic research; and3. since 1990 significant results have been achieved in modernising the curricula of economics and management studies.In the article, the theoretical concepts prevailing in Lithuania arc analysed against the background of the development of the world’s economic thought.